ACCUPRESSURE PROGRAM AT THE HEALTH CENTERS IN SOUTH JAKARTA IN 2018 - Rini, Sandra Octaviani Dyah Puspita; Achadi, Anhari (Journal of Indonesian Health Policy and Administration, 2019)
Traditional Health Services is a treatment or therapy using methods and medication that is based on the experience and skills of our ancestors that can be accounted for and is in accordance with the norms prevailing in the community. One example is acupressure, ehich is a healing method that uses pressure on certain points of the body or acupuncture points. This type of service has been regulated in various laws on traditional health. However, not all Health Centers provide this service. In South Jakarta City, there are only two Health Centers that provide acupressure services. This is a qualitative research, and aims to analyze the policies and implementation of the implementation of acupressure services in the Health Centers and its obstacles. The data was collected through in-depth interviews and document review. In this study we found that the quality and quantity of health workers trained in acupressure and their comprehension of the program was inadequate. In addition, the room for acupressure is only found in health centers that have provided this service. Communication is still a problem, because there is no regulation socialization regarding the regulation of acupressure services for policy implementers. However, 60% of patients were satisfied with the services provided.